2020
DOI: 10.5688/ajpe7885
|View full text |Cite
|
Sign up to set email alerts
|

Use of Learning Style Frameworks in Health Science Education

Abstract: Objective. To review the literature regarding the use of learning style frameworks in health science education, with particular attention to learning outcomes and use for self-awareness. Findings. Of the 415 articles identified in an initial search of the literature, 31 articles involving learning style frameworks were included after screening titles, abstracts, and full texts. Multiple learning style frameworks, including VARK, Kolb Learning Style Inventory, Honey and Mumford Learning Style Questionnaire, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 30 publications
1
22
0
5
Order By: Relevance
“…The term “assessment” refers to a wide variety of validated, standardized methods or tools that mentors can use to evaluate, measure, and document their current state and their readiness for growth. These frameworks are available in numerous designs, but all are intended to measure and elucidate an element of character, behavior, dispositions, and/or temperament [ 65 ]. There are a number of assessments that are widely used for the development of self-knowledge that is critical for mentors.…”
Section: Practices In a Mentor Developmental Frameworkmentioning
confidence: 99%
“…The term “assessment” refers to a wide variety of validated, standardized methods or tools that mentors can use to evaluate, measure, and document their current state and their readiness for growth. These frameworks are available in numerous designs, but all are intended to measure and elucidate an element of character, behavior, dispositions, and/or temperament [ 65 ]. There are a number of assessments that are widely used for the development of self-knowledge that is critical for mentors.…”
Section: Practices In a Mentor Developmental Frameworkmentioning
confidence: 99%
“…The impact of learning style on academic performance of students has been previously verified in studies [ 10 14 ]. Several learning-style frameworks have been employed in different health science educational disciplines [ 1 , 15 ]. Felder and Soloman’s Index Learning Style (ILS) tool describes the characteristic preferences and strengths, regarding the ways that students receive and process information [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that in order to provide a learning experience in practical courses for nursing that is able to improve cognitive abilities and critical thinking during clinical period; the flipped-learning method is used to carry out online practical courses. As for the implementation procedure, students are first asked to read (pre-reading) and then will be given a quiz, this session is vital to increase self-awareness of learning needs [23]. During synchronous lectures, clinical scenarios are made in the form of clinical cases or problems to illustrate the clinical relevance of the subject matter being taught by requiring students to identify these clinical problems and plan nursing care through mini quizzes.…”
Section: Discussionmentioning
confidence: 99%